Dampak Akibat Implementasi Program JKN Terhadap Biaya Kesehatan di Fasilitas Kesehatan Tingkat Lanjutan - Annisa Nurul Arofah; Viva Maiga Mahliafa Noor; Febri Endra Budi Setyawan; Dafa Azmi Syauqi Shihab (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2022)
The current implementation of JKN brings major changes in the health care and financing system, especially in hospitals. The payment system in hospitals has changed, which previously used a fee-for-service system, was changed to a prospective payment system using the INA-CBGs rate and BPJS Kesehatan was appointed as the implementing institution for the program. The INA-CBG's payment system was chosen because it is possible to control health costs, encourage quality services according to standards, limit unnecessary or excessive health services and encourage providers to carry out cost containment. This study aims to determine the impact of the implementation of the JKN program on health costs in FKTL. This research is a literature review (narrative review) by conductinga literature review of 12 journals. Journals were obtained from Google Scholar and PubMed searches with the keywords Impact of JKN on Healthcare Costs in FKTL OR Hospitals which were selected with the criteria of national and international journals with good reputation and indexed by SINTA and SCOPUS which were published no later than 2016. the purpose of this study and passed the selection. The results of the analysis show that the impact of JKN, especially on health costs, has an effect on the pattern ofJKN utilization by the community, patient satisfaction, hospital efficiency, Gross Profit Margin and Net Profit Margin of hospitals, and has an effect on hospital income. It can be concluded that there has been an influence on FKTL since the JKN era entered Indonesia.